Designing a composite solidification agent to improve mechanical properties and sulfate resistance of construction clay-residue. (15th September 2022) - Jin, Jiaxu; Qin, Zhifa; Yang, Hui; Zuo, Shenghao; Song, Chenguang
Abstract: The utilization of construction clay-residue (CCR) through solidification treatment reduces the waste of land resources and environmental pollution. In this paper, a new composite solidification agent (CSA) containing calcined silt (CS), fly ash (FA), and ground granulated blast-furnace slag (GGBS) is designed to improve the performances of solidified CCR. The optimum proportion of CSA was determined based on the orthogonal test design and response surface methodology (RSM). The effects of CSA incorporation on the properties of CCR were investigated and compared with CCR solidified by ordinary Portland cement (OPC). The results indicate that the use of CSA in solidified CCR slightly decreases the unconfined compressive strength in comparison with OPC, however, significantly improves the resistance to sulfate attack. The strength reduction and mass loss of the CSA-solidified CCR after 28 cycles were less than that of the OPC-solidified CCR. Thus, the designed CSA is recommended to solidify CCR in engineering practice for economic and environmental benefits and better durability. Highlights: The CSA was designed as a ternary blend of pozzolanic material, cement, and lime. The mass proportions of CS, FA, and GGBS in pozzolanic material were determined by the simplex-lattice design. CSA-solidified CCRs showed better durability and comparable strength in comparison with OPC-solidified CCRs.